(The Study of Pineapple and Soursop Jam Slices Formulation) - Solechan -; Irma Susanti (Balai Besar Industri Agro, 2005)
Research on the formulation of jam slices from pineapple and soursop has been conducted.The objective of this research is to obtain the best formula for jam slices making from pineaplle and soursop.The treatment used for pineapple jam slices were mixed pineapple peree with sugar and glucose wiyh ratio (100:0):(67:33),(50:50)w/w,respectively,margarine (3%:5%),citric acid and benzoat,than cooked until its thicked amd added margarine to made the jam being slices.The resul showed that the formula with 100% sugar and 5% margarine was the best pineapple jam slices formula according to the organoleptic test conducted.The result of water content analysis from the best formulation of pineapple jam slices showed 10.9%,total sucrose 72.4%,pH 3.93 and TPC 75 coloni/gram.Therefore 100% sugar without glucose mixing should be used for making jam slices.The treatment for making soursop jam slices were butter (1,5%,3%;5%)and agar (0.2%,0.4% and 0.6%). The result showed that the formula with 3% butter and 0.2% agar was the best soursop jam slices formula according to organoleptic test.The result of water content analysis from the best formulation of soursop jam slices showed 14.8%, total sucrose 64.6%,pH 3.99,and TPC 1.9 X 10 kuadrat coloni/gram.